Comparison study of student with special educational need in elementary school - Erdei, Norbert (Acta Agraria Debreceniensis, 2014)
The aim of this lecture is to observe the status of students with special educational needs (SEN) in Europe and Hungary. The European Union has made tough decisions in financing and educating disabled people, so they can be integrated into the society. According to the European directives, Hungarian jurisdiction and educational politics tend to follow the pedagogical processes. The relevant juridical and economical laws for SEN students have already been implemented. The number of students with SEN in Europe increases permanently, so it is reasonable to detect their controversy. Despite this fact, differences can be experienced in teaching methods among primary schools, as a result development of SEN students can be different. The aim of this study to compare the motor skills of SEN students in two different primary schools, with different pedagogical program. My research base were the Ferenc Móra primay school and Gyermekház alapítvány primary school in Budapest. My main question was, if a specially developed program targeted SEN students can increase their motor skills. Studying the girls in the 2 age-groups, we have not experienced significant differencies out of the 3 motor tests between the control and the experimental groups.Studying the boys in the 2 age-groups, we have experienced 3 significant differencies out of the 3 motor tests between the control and the experimental groups. SEN students, who have been taught in segregated form with the help of ’Alapozó Terápia’ – a special therapy – achieved better motor skills. The study makes recommendation to primary shools how to organise trainigs for these students.